The Urgency of Fiqh Rules Regarding Differences in Eid al-Adha Determination in Indonesia - Alimuddin, Harwis; Anwar, Khairil (Universitas Islam Negeri Alauddin Makassar, 2022)
Variations in Eid al-Adha determination is due to the differences in ascertaining the beginning of the Islamic month of Zulhijjah. Furthermore, the discrepancies in establishing the beginning of the Zulhijjah month are due to differences in maţla, which is the location where the new moon appears, as well as variations in the reckoning and ru'yah methods. A qualitative method was used for evaluating, characterizing, and exposing its findings. The method of data collection was literature review, which aims to investigate the origins of differences and discover a compromise solution to decrease or eradicate these variations, or at least to comprehend those that cannot be eliminated. The results showed variations in the location from which the new moon is viewed as well as the methodologies used lead to differences in establishing the beginning of the Zulhijjah month. This leads to differences in the schedule of holidays. Therefore, determining the beginning of the Zulhijjah month needs to be carried out by the leader of the jurisdiction or legal area. There are also disparities in holiday determination due to differences in jurisdictions which cannot be avoided. Hence, the government's decision of one jurisdictional area can remove discrepancies in its territory ḥukm al-ḥākim yarfa'u al-khilāf.